The Duckling Gets a Cookie!? - Willems, Mo (New York Hyperion Books for Children, 2012)
Pigeon is very angry when the duckling gets a cookie just by asking politely.
Keywords: Pigeons -- Juvenile fiction; Ducks -- Juvenile fiction; Cookies -- Juvenile fiction; Etiquette -- Juvenile fiction; Pigeons. -- Fiction; Ducks -- Fiction; Cookies -- Fiction; Etiquette -- Fiction; Humorous Stories